Міжнародна правова допомога в кримінальному провадженні - Мартовицька, О. В.; Martovytska, O. V.; Олена Мартовицька (Юридична наука. - 2019. - № 11 (101), т. 1. - С. 468-473, 2019)
Запропоновано під міжнародною правовою допомогою розуміти різновид юридичної діяльності, який полягає в здійсненні уповноваженими законодавством України суб’єктами своїх повноважень з проведення процесуальних дій з метою забезпечення здійснення досудового розслідування, судового розгляду або виконання вироку, ухваленого судом іншої держави або міжнародною судовою установою задля реалізації, охорони та захисту гарантованих державою прав, свобод і законних інтересів людини.

In the article, it has been emphasized the need to clarify the nature and content of international legal assistance in criminal proceedings in both the scientific legal literature and national law in order to determine its place and relationship with the institution of legal assistance. It has been found that, although the issue of international cooperation in criminal proceedings and its forms has often been studied in the works of both domestic and foreign scholars, many issues still remain controversial or unresolved. Scientific approaches to the interpretation of the concept of “international legal assistance”, “international cooperation in criminal proceedings” have been analyzed. It has been noted that at the legislative level the term “international legal assistance” and its interpretation are enshrined in the Criminal Procedure Code of Ukraine. The features of international legal assistance, which determine its essence and significance in criminal proceedings, have been singled out and characterized. It has been emphasized that no less important scientific task is to find out the place of international legal aid in the legal aid system. It has been found that international legal aid and legal aid are related as separate and general, respectively. It has been stated that international legal assistance is a type of legal activity that consists in the application of legal remedies aimed at facilitating a pre-trial investigation, trial or execution of a sentence passed by a court of another state or an international judicial institution. It has been noted that international legal assistance is a specific type of legal assistance, as its implementation of procedural actions will further ensure the proper provision of legal services in order to ensure state-guaranteed human rights and freedoms. The content of international legal assistance in criminal proceedings has been clarified.

Предложено под международной правовой помощью понимать разновидность юридической деятельности, которая заключается в осуществлении уполномоченными законодательством Украины субъектами своих полномочий по проведению процессуальных действий с целью обеспечения осуществления досудебного расследования, судебного разбирательства или исполнения приговора, вынесенного судом другого государства или международным судебным учреждением для реализации, охране и защите гарантированных государством прав, свобод и законных интересов человека.
International legal assistance in criminal proceedings
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; міжнародна правова допомога; international legal assistance; международная правовая помощь; міжнародне співробітництво; international legal assistance; международная правовая помощь; законодавство; legislation; законодательство